Quantitative losses and quality of cotton: influence of delayed harvest and insertion of the boll on the plant (Research, Society and Development, 2021)
The harvest is one of the most important processes in the cotton production chain, since it is the period of greatest exposure to bad weather, dust, and deposition of leaf particles and other materials, which can cause a reduction in fiber quality and lead to lint loss if harvesting is delayed. Thus, the objective of this study was to evaluate the quantitative pre-harvest losses and the fiber quality of two cotton cultivars (FM 944GL e TMG 81 WS), as a function of the delay in harvest and the position of the boll on the plant. The pre-harvest losses were measured in three stages, the first at the moment considered ideal for harvesting, followed by two other harvest stages later, configuring delays. The fiber quality was determined according to the insertion of the boll on the plant: upper, middle, and lower thirds. The analyses of the fiber characteristics were performed at COOAMI's Fiber Classification Laboratory using the HVI apparatus. Delayed harvesting increased quantitative losses in soil during pre-harvest and of impurity particles in the fiber, and reduced elongation, micronaire index, and color grade. The cultivar FM 944GL showed better performance in most of the fiber quality characteristics. Finally, the upper third on the plant showed better quality.